2011
DOI: 10.1007/s11604-010-0539-5
|View full text |Cite
|
Sign up to set email alerts
|

Infraorbital nerve swelling associated with autoimmune pancreatitis

Abstract: Infraorbital nerve swelling was observed more frequently in AIP patients than in patients without a history of AIP. Therefore, such swelling seems to be an extrapancreatic lesion of AIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…In IgG4-related orbital diseases, it is known that the major lacrimal gland and other soft tissues of the orbit may be involved. Moreover, it is reported that lesions can involve the orbital nerve [7,8]. Until now, little attention has been paid to the In this study, IONE was only observed in IgG4-related orbital diseases and MALT associated with IgG4-related orbital diseases, whereas it was not observed in MALT which does not associate with IgG4-related orbital diseases, RLH, or idiopathic orbital inflammation, which are not related to IgG4.…”
Section: Discussionmentioning
confidence: 54%
“…In IgG4-related orbital diseases, it is known that the major lacrimal gland and other soft tissues of the orbit may be involved. Moreover, it is reported that lesions can involve the orbital nerve [7,8]. Until now, little attention has been paid to the In this study, IONE was only observed in IgG4-related orbital diseases and MALT associated with IgG4-related orbital diseases, whereas it was not observed in MALT which does not associate with IgG4-related orbital diseases, RLH, or idiopathic orbital inflammation, which are not related to IgG4.…”
Section: Discussionmentioning
confidence: 54%
“…11,19,20 Cerebral involvement in IgG4-RD is rarely reported, with most cases relating to either retro-orbital involvement (with associated infra-orbital nerve swelling 21 and visual fi eld defects 22 ) or to pituitary disease (Table 1). 15,16,23 Non-infectious hypertrophic pachymeningitis, infl ammation and subsequent thickening of the dura mater (cranial or spinal) is regarded as another neurological manifestation of IgG4-RD.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have also reported the presence of perineural spread of IgG4-related disease, with expansion of the associated neural foramina. 4,8,9,17,18 Limitations of our study include its retrospective nature. Additionally, the imaging-acquisition parameters were not consistent among all patients.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Although initially described in association with autoimmune pancreatitis, manifestations of IgG4-related disease are now reported in nearly every organ system. [1][2][3][5][6][7][8][9][10] Multiple case reports and small case series of orbital manifestations of IgG4-related disease have noted involvement of the extraocular muscles, lacrimal glands, and infraorbital nerve, 1,2,4,[7][8][9][10][11][12][13][14][15][16][17][18][19] but these small series do not allow evaluation of the typical patterns of imaging findings in IgG4-related disease. The purpose of this study was to retrospectively identify the spectrum of imaging features seen in IgG4-related disease of the orbit.…”
mentioning
confidence: 99%